Effects of the Interactive Use of Performance Measurement Systems on Job Performance: Mediation Effect of Organizational Learning - Zhang, Lu; Yu, Wenjun (Frontiers in Psychology, 2020)
Interactive controls, focusing on communication and continuous learning, are very important to achieve a competitive advantage. In order to better understand the underlying mechanism of how performance measurement systems (PMS) improve job performance, a mediation model was constructed in current study to examine organizational learning as a possible mediating variable. Data were collected using a questionnaire in China with a sample size of 191 managers. Structural equation model and Smart-PLS methods were used to test the hypotheses. Results yielded significant direct effects between the interactive use of PMS on organizational learning and job performance. Additionally, organizational learning was found to play a mediating role in the relationship between interactive use of PMS and job performance. These findings highlight the importance of interactive PMS use, as well as the underlying mechanisms among PMS, organizational learning, and job performance, and further help the management clarify how organizational learning affects performance, providing a framework for building a sustainable competitive advantage.